Assessment of the Efficiency of Consolidation Treatment through Injections of Expanding Resins by Geotechnical Tests and 3D Electrical Resistivity Tomography. (17th June 2015) - Apuani, T.; Giani, G. P.; d'Attoli, M.; Fischanger, F.; Morelli, G.; Ranieri, G.; Santarato, G.
Abstract : The design and execution of consolidation treatment of settled foundations by means of injection of polyurethane expanding resins require a proper investigation of the state of the foundation soil, in order to better identify anomalies responsible for the instability. To monitor the injection process, a procedure has been developed, which involves, in combination with traditional geotechnical tests, the application of a noninvasive, geophysical technique based on the electrical resistivity, which is strongly sensitive to presence of water or voids. Three-dimensional electrical resistivity tomography is a useful tool to produce effective 3D images of the foundation soils before, during, and after the injections. The achieved information allows designing the consolidation scheme and monitoring its effects on the treated volumes in real time. To better understand the complex processes induced by the treatment and to learn how variations of resistivity accompany increase of stiffness, an experiment was carried out in a full-scale test site. Injections of polyurethane expanding resin were performed as in real worksite conditions. Results confirm that the experimented approach by means of 3D resistivity imaging allows a reliable procedure of consolidation, and geotechnical tests demonstrate the increase of mechanical stiffness.